Hybrid defense mechanism against malicious packet dropping attack for MANET using game theory - S Vijayalakshmi; S Bose; G Logeswari; T Anitha (Cyber Security and Applications)
Ad hoc networks are a new perspective of wireless communication for versatile hosts. Security is a colossal worry for ad hoc networks, especially for those security-touchy applications. The huge highlights of ad hoc networks cause both difficulties and openings in accomplishing security objectives. One such aim is to consider the assaults from within the system by compromised nodes correspondingly as to consider harmful assaults propelled from outside the system. Designing an Intrusion Detection System (IDS) that suits the security needs and characteristics of ad hoc networks for viable and proficient performance against intrusions is one potential solution to vanquish vulnerabilities. This paper examines a genuine and hurtful attack called, “Malicious Packet Dropping Attack” in the network layer. To secure against this attack, a novel methodology utilizing game theory is proposed. The proposed system monitors the conduct of the neighbor nodes and conquers the demerits such as false positives present in traditional IDS, thereby providing secure correspondence between nodes that communicate with one another to course the traffic from source to destination. With the existence of malicious nodes, the proposed system has accomplished a 42% increase in the packet delivery ratio.